The Importance of DNA Profiling Today - V. Basil Hans (International Journal of Genetic Modifications and Recombinations, 2026)
DNA profiling has changed a lot of sectors, from health and criminal justice to ancestry research and animal conservation. It is one of the most important scientific instruments of our time. This technique makes it possible to identify people, analyse family relationships, and learn more about biology by looking at unique genetic markers in a person's DNA. DNA profiling has changed the way forensic science works by making it easier to find suspects, clearing innocent people, and making court cases more likely to end in a fair decision. DNA profiling has made progress in many areas besides forensics. It supports personalised medicine by allowing for therapies that are specific to a person's genetic makeup. It also helps with population genetics, evolutionary studies, and protecting biodiversity. Even while DNA profiling has many benefits, its broad usage creates ethical, legal, and privacy problems, especially when it comes to data security, permission, and possible misuse. This article talks about the scientific basis of DNA profiling, its many uses in today's world, and the problems that come with its quick growth. It stresses the necessity for responsible governance to make sure that its benefits are realised while protecting people's rights. DNA profiling works on the idea that, although while human DNA is mostly the same across different groups of people, some parts of the genome are different enough to tell one person from another. Scientists can make genetic profiles that are statistically strong and very dependable by looking at these changeable regions. The improvement of lab techniques, along with better computer analysis and database administration, has made DNA profiling technology much faster, more accurate, and easier to use. DNA profiling has changed the way criminal investigations are done in forensic and judicial settings by giving investigators objective biological evidence that can connect suspects to crime sites or clear them of suspicion. Its use has made judicial systems around the world stronger by making it more likely that people will be found guilty and by facilitating reviews after a conviction. DNA profiling is very important for medical diagnosis, personalised treatment plans, ancestry testing, determining paternity, and protecting endangered species.
Keywords: Forensic science; and modern biotechnology; ethical issues; genetic identification; personalised medicine